Species identification of Aspergillus section Flavi isolates from Portuguese almonds using phenotypic, including MALDI-TOF ICMS, and molecular approaches - Rodrigues, P. (2011)
Aims: Section Flavi is one of the most significant sections in the genus Aspergillus. Taxonomy of this section currently depends on multivariate approaches, entailing phenotypic and molecular traits. This work aimed to identify isolates from section Flavi by combining various classic phenotypic and genotypic methods as well as the novel approach based on spectral analysis by matrix-assisted laser desorption ⁄ ionization time-of-flight mass spectrometry (MALDI-TOF ICMS) and to evaluate the discriminatory power of the various approaches in species identification. Methods and Results: Aspergillus section Flavi isolates obtained from Portuguese almonds were characterized in terms of macro- and micromorphology, mycotoxin pattern, calmodulin gene sequence and MALDI-TOF protein fingerprint spectra. For each approach, dendrograms were created and results were compared. All data sets divided the isolates into three groups, corresponding to taxa closely related to Aspergillus flavus, Aspergillus parasiticus and Aspergillus tamarii. In the A. flavus clade, molecular and spectral analyses were not able to resolve between aflatoxigenic and nonaflatoxigenic isolates. In the A. parasiticus cluster, two well-resolved clades corresponded to unidentified taxa, corresponding to those isolates with mycotoxin profile different from that expected for A. parasiticus.